Интеллектуальные возможности и перспективы развития фазаграфии — информационной технологии обработки сигналов сложной формы - Файнзильберг, Л.С. (Кибернетика и вычислительная техника, 2016)
Сформулированы основные свойства интеллектуальных информационных технологий обработки сигналов сложной формы. Показано, что основные функции метода фазаграфии соответствуют этим свойствам. Приведены новые научно-практические результаты использования программно-технического комплекса ФАЗАГРАФ® в детской кардиологии. Намечены перспективные пути развития технологии для решения актуальных прикладных задач. Сформульовано основні властивості інтелектуальних інформаційних технологій обробки сигналів складної форми. Показано, що основні функції методу фазаграфії відповідають цим властивостям. Наведено нові науково-практичні результати використання програмно-технічного комплексу ФАЗАГРАФ® в дитячій кардіології. Окреслено перспективні шляхи розвитку технології для вирішення актуальних прикладних задач. The purpose of the article is — to formulate the basic properties of intelligent IT complex form signal processing, demonstrate the ability to implement these features on the example of the innovative method fasegraphy and outline prospects for further development of this technology. Results. Basic properties of intelligent IT — adaptation, learning, generalization, invariance, forecasting, understanding, flexibility, interoperability, accessibility have been formulated. Analysis of computational procedures chain in fasegraphy method, that provide a transition from the actually observed signals to technology product, shows that the method has all of the above properties, and therefore fasegraphy can be referred to intelligent ITs.